2007
DOI: 10.1007/s11065-007-9021-2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Neuropsychological Symptoms of Adolescents and Adults with PKU

Abstract: Phenylketonuria (PKU; OMIM 261600) is an autosomal recessive inborn error of phenylanaline metabolism. PKU is characterized by deficient or defective phenylalanine hydroxylase activity and persistantly increased levels of the essential amino acid phenylalanine in the circulation. The present article examines current understanding of the etiology of PKU, along with a meta-analysis examining neuropsychological and intellectual presentations in continuously treated adolescents and adults. Patients with PKU differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1
24

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 79 publications
8
135
1
24
Order By: Relevance
“…[66][67][68] Much literature on early and continuously-treated PAH deficiency reports IQ scores in the average range; however, pediatric data suggest that even under these circumstances, children with PAH deficiency attain IQ scores that are six to nine points lower than their siblings and parents. 69,70 Even in a non-PAH-deficient population, IQ scores only partially correlate with school grades and academic achievement, 71 and therefore further assessment beyond IQ testing is needed for full definition of functional outcomes of management and treatment. 69 Notably, although studies have not been uniform, deficits in executive function in individuals with PAH deficiency are consistent enough to warrant special attention.…”
Section: Acmg Practice Guidelines Neurocognitive and Psychological Oumentioning
confidence: 99%
See 1 more Smart Citation
“…[66][67][68] Much literature on early and continuously-treated PAH deficiency reports IQ scores in the average range; however, pediatric data suggest that even under these circumstances, children with PAH deficiency attain IQ scores that are six to nine points lower than their siblings and parents. 69,70 Even in a non-PAH-deficient population, IQ scores only partially correlate with school grades and academic achievement, 71 and therefore further assessment beyond IQ testing is needed for full definition of functional outcomes of management and treatment. 69 Notably, although studies have not been uniform, deficits in executive function in individuals with PAH deficiency are consistent enough to warrant special attention.…”
Section: Acmg Practice Guidelines Neurocognitive and Psychological Oumentioning
confidence: 99%
“…65,66,70,[84][85][86] Symptom severity correlates with elevation in PHE, and reduction of PHE generally results in symptom improvement. Numerous studies suggest an increased prevalence of attention problems and attention deficit-hyperactivity disorder in PAH deficiency; as many as 25% of the children with early-treated PAH deficiency receive stimulant medication for treating attention deficit-hyperactivity disorder as compared with 7% of the children with diabetes.…”
Section: Psychological Issuesmentioning
confidence: 99%
“…[11][12][13] Despite functioning within the average range on tests of intelligence, children and adults with PKU have a lower mean intelligence quotient (IQ) than the general population. 12,14,15 Deficits affecting language skills, visual-spatial abilities, processing speed, verbal comprehension, and perceptual reasoning skills have also been reported. 13,[16][17][18][19][20] A meta-analysis of Phe levels and IQ in 40 studies confirmed a significant negative correlation between blood Phe levels and IQ in individuals with PKU who were treated early.…”
Section: Introductionmentioning
confidence: 99%
“…The cost, inconvenience, and sometimes difficult access to PKU diet increase the difficulty of adhering to it. Although there is still debate over whether adult PKU patients need a strict phenylalanine-restricted diet and despite the fact that there are some adults with PKU who do not follow a restricted diet and lead normal lives, many studies have advocated following a restricted diet in adulthood as it has been shown that high phenylalanine levels in adults can have adverse effects on mood, sustained attention, concentration, and cognitive ability (Feillet et al 2010b;Ten Hoedt et al 2011;Macdonald et al 2010;Moyle et al 2007;Simon et al 2008). Restricted diet is also crucial in female adults with PKU planning for a pregnancy, as maternal PKU has been shown to cause fetal abnormalities including microcephaly, congenital heart disease, and mental retardation (Prick et al 2012).…”
Section: Discussionmentioning
confidence: 99%